Hot corrosion resistance of Zrb2-based ceramic composites against NaCl molten salt. (April 2015) - Zhou, S. B.; Gao, J. X.; Hu, P.; Cheng, Y. H.; Wang, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Hot corrosion resistances of ZrB2–SiC–C ceramic composites were studied at 1000°C in molten NaCl. Results indicated that the sample underwent a slight corrosion. Both macrograph and microstructure of the composites exhibited no obvious change. The ZrB2–SiC–C composite showed good resistance to [Cl−] corrosion in high temperature.